2012
DOI: 10.4238/2012.may.21.1
|View full text |Cite
|
Sign up to set email alerts
|

Meta analysis of angiotensin-converting enzyme I/D polymorphism as a risk factor for preeclampsia in Chinese women

Abstract: ABSTRACT. Preeclampsia affects 3-8% of pregnancies and is a major cause of maternal and perinatal morbidity and mortality worldwide. Inappropriate activation of the renin-angiotensin system may play a role in the development of preeclampsia. An insertion/ deletion polymorphism in the angiotensin-converting enzyme gene (ACE-I/D) has been associated with differences in ACE activity. However, there are controversies in reports on the association of ACE-I/D with preeclampsia. Data were analyzed using Review Manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
2
27
0
1
Order By: Relevance
“…I 2 values of 25, 50, and 75% were defined as low, moderate, and high estimates, respectively. When I 2 > 50%, heterogeneity was indicated across studies and the random-effect model was used for meta-analysis; otherwise, the fixed-effect model was used (Zhou et al, 2011;Zhong et al, 2012). Stratified analysis was performed according to ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…I 2 values of 25, 50, and 75% were defined as low, moderate, and high estimates, respectively. When I 2 > 50%, heterogeneity was indicated across studies and the random-effect model was used for meta-analysis; otherwise, the fixed-effect model was used (Zhou et al, 2011;Zhong et al, 2012). Stratified analysis was performed according to ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…35,[37][38][39] A large study (more than 1000 Caucasian women) conducted by Pfab with coworkers did not reveal the association of I/D polymorphism of the ACE gene with BP level during a pregnancy. 40 Meantime, a meta-analysis of more than 50 studies showed a significant association of the I/D polymorphism with PIH and preeclampsia in Chinese, 41,42 and in Asians and Caucasians. 43 The observed inconsistency in the above results may be explained by inter-population and interethnic differences in the distribution of the I/D polymorphism: allele D is predominant in Caucasians from Europe, Australia and the USA, whereas allele I is more prevalent among Chinese and Indians.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the findings related to the genetic polymorphism of ACE in PE results in different data. Perhaps this contradiction is based on the analysis of distinct populations, with them having differing ethnic and genetic characteristics [28][29][30][31][32].…”
Section: Urinary Detection Of the 90 Kda Ace Isoformmentioning
confidence: 97%
“…Studies on the genetic polymorphism of the angiotensin-converting enzyme (ACE), one of the components of the RAS, demonstrate that the D allele is related to elevated plasma ACE levels, and is strongly associated with cardiovascular diseases [27]. However, the findings concerning ACE genetic polymorphism in PE are contradictory [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 98%